2020
DOI: 10.33979/2073-7408-2020-344-6-58-61
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Bending With Application of Active Friction Forces

Abstract: An engineering analysis of pipe bending along a circular copier with a deviation of flat material sections from the normal (by Love) position is performed, the dimensions of the active deformation area and the reactions of tools that generate friction forces are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, general recommendations on the limits of bend parameters, which can be found in the general literature, are insufficient. For example, in [4] it is indicated that bending of pipes of circular cross-section with diameter D without mandrel is possible provided: ( ) min 2...3 RD = (5) and with mandrel the limits expand to:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, general recommendations on the limits of bend parameters, which can be found in the general literature, are insufficient. For example, in [4] it is indicated that bending of pipes of circular cross-section with diameter D without mandrel is possible provided: ( ) min 2...3 RD = (5) and with mandrel the limits expand to:…”
Section: Discussionmentioning
confidence: 99%
“…These calculation methods should allow the justification of the required bend parameters and thereby reduce the number of test bends of the work pieces and, accordingly, the time and resources that in this case will be necessary only to confirm the correctness of the calculations. Many scientific works [1][2][3][4][5][6] are devoted to this area, in which classical and new hybrid calculation methods are proposed. However, these methods require high-performance computers, long calculation time and high qualification of the calculator, which is not applicable under usual conditions.…”
Section: Introductionmentioning
confidence: 99%